Twenty trucks [videorecording (DVD)] : can you name twenty trucks? I bet you can! (Hammershark Media, 2004)
Twenty Trucks shows 20 different trucks "doing their jobs", accompanied by the real sounds of the trucks and simple narration explaining the job that each truck performs.